Saponins accumulation and antimicrobial activities on shallot (Allium cepa L.) from marginal land - Ariyanti, Nur Aeni; Latifa, Sonia (Jurnal AGRO, 2022)
Saponins are one of the secondary metabolites found in Shallot (Allium cepa L.), particularly in the roots. Microclimate differences in the cultivation area are thought to have a significant impact on the production of secondary metabolites, such as saponins. This research aimed to observe the saponins content in the root of shallot plants cultivated in marginal agricultural land and their antimicrobial activity against bacteria (Ralstonia solanacearum) and fungus (Fusarium oxysporum). This research was observational research with a random sampling method. The samples were collected from the shallot plantation with two different cultivation conditions. Two varieties of ‘Bima' and 'Tiron' cultivated by farmers in sandy coastal land Samas, Bantul were used. The plants were harvested at 1, 1.5, and 2 months after planting, respectively. The crude saponins extract was used to test antimicrobial activity. Shallot plants cultivated in marginal coastal sandy land produced higher saponins accumulated in their roots. The saponins production increased along with the maturity of shallot plants, both cultivated in marginal coastal sandy land and regular paddy field. The saponins extracted from the roots of shallots cultivated in both marginal and regular land showed higher antimicrobial activity than antifungal activity. Saponin merupakan salah satu metabolit sekunder yang terdapat pada bawang merah (Allium cepa L.), terutama pada bagian akar. Perbedaan iklim mikro pada lahan budidaya diduga akan berpengaruh terhadap produksi metabolit sekunder termasuk saponin. Tujuan penelitian ini adalah untuk mengetahui kandungan saponin pada bagian akar tanaman bawang merah yang dibudidayakan di lahan pertanian marginal serta aktivitas antimikrobanya terhadap bakteri (Ralstonia solanacearum) dan jamur (Fusarium oxysporum). Penelitian ini merupakan penelitian observasi dengan metode pengambilan sampel secara acak. Sampel berasal dari perkebunan bawang merah dengan dua lahan budidaya yang berbeda. Digunakan dua varietas yaitu 'Bima' dan 'Tiron' yang dibudidayakan oleh petani di daerah pantai Samas,kabupaten Bantul. Bahan tanaman dipanen pada tiga waktu berbeda, yaitu 1 bulan, 1,5 bulan dan 2 bulan berturut-turut setelah tanam. Ekstrak kasar saponin digunakan untuk menguji aktivitas antimikrobanya. Tanaman bawang merah yang dibudidayakan di lahan marginal pasir pantai menghasilkan saponin yang lebih tinggi yang terakumulasi pada akarnya. Produksi saponin semakin meningkat seiring dengan umur tanaman bawang merah, baik yang dibudidayakan di lahan marginal pasir pantai maupun di lahan sawah biasa. Saponin yang diekstraksi dari akar bawang merah yang dibudidayakan di lahan marginal dan lahan biasa menunjukkan aktivitas antimikroba yang lebih tinggi daripada aktivitas antijamurnya.